Group A Streptococcal Pharyngeal Infections: Diagnosis and Rational Antibacterial Therapy - B. S. Belov (Антибиотики и Химиотерапия)
The problem of acute tonsillitis caused by Group A Beta-Hemolytic Streptococcus (GABHS) still remains relevant. This article provides data showing the revival of highly virulent GABHS infection and an increase in the incidence of complications (acute rheumatic fever, toxic shock syndrome), and substantiates the need for rational antibiotic therapy of this pathology. The drugs of choice for the treatment of acute forms of GABHS tonsillitis are penicillins and cephalosporins of the first generation, and macrolides in case of intolerance to beta-lactam antibiotics. In the presence of chronic relapsing GABHS tonsillitis, when the probability of colonization of the source of infection by microorganisms producing beta-lactamases is high enough, inhibitor-protected penicillins or cephalosporins of II-III generation are used. Lincosamide antibiotics are used in the treatment of acute and chronic GABHS tonsillitis as reserve drugs.